2000
DOI: 10.1089/10445470050144029
|View full text |Cite
|
Sign up to set email alerts
|

Gallium Diffusion in Human Root Dentin: Quantitative Measurements by Pulsed Nd:YAG Laser Ablation Combined with an Inductively Coupled Plasma Mass Spectrometer

Abstract: Even the lowest concentrations of gallium found in peripheral root dentin exceeded the 10(-4) M concentration required to inhibit osteoclastic activity. This simple endodontic treatment should undergo clinical trials to determine its efficacy in vivo. The laser ablation, inductively coupled mass spectrometry method is a powerful analytic tool for measuring spatial distribution of materials in mineralized tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 20 publications
1
20
0
Order By: Relevance
“…This was consistent with previous reports, where gallium nitrate was placed in human root canals to assess whether it would diffuse across root dentine and reach concentrations high enough to inhibit osteoclasts [Ghazi et al, 2000]. The report showed that the gallium concentration was highest adjacent to the root canal space and fell as more peripheral sites were sampled, but then rose slightly at the external boundary of the root which is covered with a thin layer of a tubular cementum [Ghazi et al, 2000].…”
Section: Activity Of Gallium On S Mutans and Dental Tissuessupporting
confidence: 90%
See 1 more Smart Citation
“…This was consistent with previous reports, where gallium nitrate was placed in human root canals to assess whether it would diffuse across root dentine and reach concentrations high enough to inhibit osteoclasts [Ghazi et al, 2000]. The report showed that the gallium concentration was highest adjacent to the root canal space and fell as more peripheral sites were sampled, but then rose slightly at the external boundary of the root which is covered with a thin layer of a tubular cementum [Ghazi et al, 2000].…”
Section: Activity Of Gallium On S Mutans and Dental Tissuessupporting
confidence: 90%
“…The report showed that the gallium concentration was highest adjacent to the root canal space and fell as more peripheral sites were sampled, but then rose slightly at the external boundary of the root which is covered with a thin layer of a tubular cementum [Ghazi et al, 2000]. It was reported that in vivo administration of Ga 3+ interferes with osseous tissue HA generation, resulting in larger and more perfect (lowered CO 3 :PO 4 ratios) crystalline structures [Bockman et al, 1986].…”
Section: Activity Of Gallium On S Mutans and Dental Tissuesmentioning
confidence: 99%
“…Investigations on Hg migration [157] and Ga diffusion across the human teeth using LA-ICP-MS were also reported [158,159].…”
Section: Teeth Analysismentioning
confidence: 99%
“…in the past, ion presence was determined through the acidulation of all of the tissue to be examined. however, it is impossible to obtain detailed results with these techniques (14). lA-icP-MS is a technique determining the ion release in the solid materials reliably and in a short time (31).…”
Section: Resultsmentioning
confidence: 99%